2007
DOI: 10.1093/jnci/djm199
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination Between Benign and Malignant Adnexal Masses by Specialist Ultrasound Examination Versus Serum CA-125

Abstract: Pattern recognition was superior to serum CA-125 for discrimination between benign and malignant adnexal masses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
131
2
10

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(149 citation statements)
references
References 37 publications
6
131
2
10
Order By: Relevance
“…Prospective validation of these simple ultrasound rules in a sample of women with adnexal masses yielded a sensitivity of 95%, a specificity of 91%, positive likelihood ratio of 10.37 and negative likelihood ratio of 0.06 56 . This study has also demonstrated that although pattern recognition of ultrasound findings by an experienced examiner can not only reproducibly discriminate between benign and malignant adnexal masses, it is superior to serum CA125 57 . The United Kingdom Collaborative Trial of Ovarian Cancer Screening (UKCTOCS) is a randomized control trial evaluating the effect of screening on mortality 58 .…”
Section: How Effective Is Ultrasound In Detecting Early Stage Ovarianmentioning
confidence: 68%
“…Prospective validation of these simple ultrasound rules in a sample of women with adnexal masses yielded a sensitivity of 95%, a specificity of 91%, positive likelihood ratio of 10.37 and negative likelihood ratio of 0.06 56 . This study has also demonstrated that although pattern recognition of ultrasound findings by an experienced examiner can not only reproducibly discriminate between benign and malignant adnexal masses, it is superior to serum CA125 57 . The United Kingdom Collaborative Trial of Ovarian Cancer Screening (UKCTOCS) is a randomized control trial evaluating the effect of screening on mortality 58 .…”
Section: How Effective Is Ultrasound In Detecting Early Stage Ovarianmentioning
confidence: 68%
“…Pattern recognition by ultrasound examination is another modality for discrimination between benign and malignant adnexal masses are considered superior to serum CA 125 estimation. 6 But this too has limitations as in our case the broad ligament leiomyoma mimicked ovarian cyst sonographically. The degenerative changes in the leiomyoma can lead to this confusion.…”
mentioning
confidence: 62%
“…The study of Benvancalster et al showed that ultrasound examiners assigned a correct specific diagnosis to at least 80% of endometriomas and 84% of dermoid cysts [21].…”
Section: Resultsmentioning
confidence: 99%
“…Clinicians remain unable to diagnose simultaneous presence of two distinct pathologies in a single ovary. Moreover, it was reported that the level of serum CA-125 is often elevated in women with endometriomas and in cystic teratomas [21].…”
Section: Discussionmentioning
confidence: 99%